International trade 1983/84 - general agreement and tariffs and trade (Geneva, 1984)
This book summarized the recovery in the world economy, while the later considers some reasons why the current recovery has failed to spread internationally to the same extent as previous post - war recoveries.
General agreement on tariffs and trade
Include bibliographical footnotes
hza 29/01/2019
Loans
Keywords: Commerce; international trade; trade agreement